Efficient and economic process for the production of bacterial cellulose from isolated strain of Acetobacter pasteurianus of RSV-4 bacterium. (March 2019) - Kumar, Vinod; Sharma, Devendra Kumar; Bansal, Vasudha; Mehta, Deepak; Sangwan, Rajender S.; Yadav, Sudesh Kumar
Highlights: Acetobacter pasteurianus RSV-4 produce bacterial cellulose on various agro-residues. Achieved more than 7 g bacterial cellulose/L of tomato juice. Optimized the process parameters of bacterial cellulose production. Abstract: In the present investigation, several residues from agro-forestry industries such as rice straw acid hydrolysate, corn cob acid hydrolysate, tomato juice, cane molasses and orange pulp were evaluated as the economical source for the production of bacterial cellulose. The bacterial cellulose attained the significant yield of 7.8 g/L using tomato juice, followed by 3.6 g/L using cane molasses and 2.8 g/L using orange pulp after 7 days of incubation. Furthermore, the optimum pH and temperature of fermentation for maximum production of bacterial cellulose was 4.5 and 30 ± 1 °C. The identified bacterium Acetobacter pasteurianus RSV-4 has been deposited at repository under the accession number MTCC 25117. The produced bacterial cellulose was characterized through FTIR, SEM, TGA and DSC and found to be of very good quality. The bacterial cellulose produced by identified strain on these various agro-waste residues could be a cost effective technology for commercial its production.